Duhkha Dalam Chandogya Upanisad dan Cara Mengatasinya - Made Joniarta (Jurnal Yoga dan Kesehatan, 2018)
The main purpose of this work is to conduct an investigation deep into the truth that reaches the step when someone becomes wise and mature to decide from all karma. The Chāndogya Upaniṣad text has been chosen to be studied in this study because this literature clearly explains the duḥkha conception. The concept of duḥkha in the Chāndogya Upaniṣad is a state of the soul that is materially bound to the physical body. When the soul is bound to the senses materially, it causes billions of desires to come out. All boundaries of these desires will throw the soul into the depths of grief (duḥkha). The way to let go of the duḥkha based on the Chāndogya Upaniṣad by understanding the atman which covers the universe, will experience unlimited happiness. Truly unlimited God is He transcends all that is. Thus Chandogya Upanisad encourages everyone to know and appreciate the true nature of the self, to be released from Dukha.